Concentrations of Polychlorinated Biphenyls (PCBs) in Phragmites australis of Shatt AL-Arab River. South of Iraq - Al-Zabad, Rafid Ahmed Taha; Ayad H. Al-Khafaji; Hamid T.AL-Saad (Al-Qadisiyah Journal of Pure Science, 2021)
ABSTRACT The concentrations of polychlorinated biphenyls (PCBs) were determined from Autumn season 2019 to summer season 2020 at six sites they are: ( Al-Qurna, Al-Deer, Al-Qarma, Al-Ashar, Abu-Al-khasib, Al-Fao ) in Shatt Al-Arab river, Basrah city, south of Iraq. water samples were taken at each site and were analyzed using gas chromatography-mass spectrometry (GC–MASS) type of Agilent 7890A for PCBs levels. The results indicate that PCBs are detected in all Phragmites australis samples and its concentrations range from 1.45 ng/g to 4.11 ng/g , 5.34 ng/g to 7.99 ng/g, 2.19 ng/g to 3.59 ng/g and 0.45 ng/g to 8.09 ng/g in Autumn, Winter, Spring and Summer seasons, respectively. The Al-Qurna and Al-Ashar sites were found to have the lowest and highest mean levels of PCBs concentrations 0.035 ng/g and 0.622 ng/g, respectively. Total congeners PCBs (PCB 18, 29, 31, 28, 44, 52, 101, 141, 149, 138,153, 189, and 194) concentrations at the Phragmite australis samples for all sites ranged from 0.45 ng/g in Al-Qurna station during summer season to 8.09 ng/g in Al-Ashar station during summer season. Σhexa-PCBs and Σtri-PCBs were dominating in comparison with others PCBs congeners. This study is a first of its kind in the region and could have available information and could be used as a baseline study in the future.